Abuse histories and attributions of sexual offenders - Jung, Sandy; Carlson, Elizabeth (My University, 2011)
The current study is an exploratory study examining the relationship between the abuse histories of 89 sexual offenders and the constructs of locus of control, sexual attitudes, general empathy, and denial. Of the 89 offenders, 14.6% were sexually abused, 13.5% physically abused, and 9% both sexually and physically abused, with 61.5% having no abuse history. Analyses indicated that motivation to change was higher for abused versus non‐abused offenders, and that those who were sexually abused had significantly more cognitive distortions about children than those who experienced physical abuse. Although no differences emerged in locus of control scores, our findings indicated that physically abused offenders were more able to take on the perspective of others than those who have not experienced physical abuse. The findings provide several avenues to pursue in examining the longstanding effects of abuse in the thinking and cognitions of sexual offenders.
Keywords: Abuse; Sex offenders; Cognitive disorders; Denial; Empathy